Development and evaluation of i-Mutawwif: A mobile language traveller guide in Arabic for mutawwif (Umrah tour guide) - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Ismail, Taufik; Zubir, Muhamad Azhar; Wan Ahmad, Wan Rusli (International Association of Online Engineering, 2018)
The explosion use of various mobile gadgets such as PC tabs, smartphones, I-Pads and so on has tremendously affected learning process and delivery of content and messages faster and faster including the creation of a new field of research that relates to language learning and mobile technologies called Mobile Assisted Language Learning or MALL. The mobile technologies are suitable for distance learners as well such as traveller’s guide and backpackers who need to communicate in certain language in a country. This paper is focusing on the development and evaluation of a mobile language guide application in Arabic language for Mutawwif (Umrah Tour Guide) via smart phones in Android supported platform. The development process was done based needs analysis process among 100 mutawwif and the evaluation on user testing session was conducted among 50 respondents and who are purposively selected from 30 mutawwif and 20 learners in Baitul Mal Professional Institute under the specialization of Diploma in Hajj and Umrah Management from 26 March until 20 April 2017. However, this paper will only be discussing the scope of development and evaluation phases in the shed of ADDIE instructional design model. Overall results indicated that his interactive mobile app prototype satisfied the users’ on their language learning for traveller’s purpose by helping the Mutawwif to communicate in Arabic more effectively.